SINERGI INTERDISIPLINER MENUJU KEMANDIRIAN MELALUI PENGABDIAN MASYARAKAT DI DESA SUNGAI NIPAH, KABUPATEN MEMPAWAH - Bapuaka, Marselus Sule; Wagner, Ivan (LPPM Universitas Panca Bhakti, 2025)
The Community Service Program (KKN) of Group 15 from Panca Bhakti University in Sungai Nipah Village was designed to foster village independence through a holistic and participatory approach. The program addressed key challenges, including limited digitalization among local MSMEs, farmers' reliance on conventional agricultural methods, low legal literacy, and insufficient awareness of environmental preservation. Implementation was carried out in collaboration with the village government and community, focusing on education, infrastructure, and agriculture. Key outcomes included enhanced legal awareness through the